Pengaruh Model Pembelajaran Tipe Talking Stick Berbantuan Media Mystery Box Terhadap Hasil Belajar Siswa Tema Sistem Sonar Pada Hewan - Latifah Fajeri; Liska Berlian; Lulu Tunjung Biru (PendIPA Journal of Science Education, 2023)
The students in the 8th grade at the 2nd Ciruas State High School still have low science education learning outcomes, marked by learning that is still centered on the teacher. The aim of this study is to find out how the learning model Talking Stick with mystery box can influence students’ learning outcomes on the theme of Sonar Systems in Animals. This type of research uses experimental quatches with a non-equivalent control group design. The Talking Stick cooperative learning model was carried out in the experimental class, while the live learning model was used in the control class. Pretest-posttest tests are used to measure cognitive abilities, while non-tests are used for measuring emotional and psychomotor abilities (observed paper). The conclusion of the research has been obtained: the influence of the learning model taught with the type of talking stick-assisted media mystery box on student learning results on the theme of sonar students in animals This is demonstrated by the acquisition of average values from both classes during the test. On the cognitive aspect, a score of 54.9 was obtained for the control class and an average of 72.3 for the experimental class. On the psychomotor aspect, we obtained a score of 77.8 in the control class and 88.2 in the experimental class. In addition, on the affective aspect, he obtained a score of 75.9 in the control class and 84.1 in the experimental class. The data showed that achievements in each cognitive, psychomotor, and affective aspect obtained the highest score in the experimental class.